Carbon dioxide controlled earthquake distribution pattern in the NW Bohemian swarm earthquake region, western Eger Rift, Czech Republic – gas migration in the crystalline basement. Issue 2 (22nd August 2013) - Weinlich, F. H.
Abstract The ascent of magmatic carbon dioxide in the western Eger (Ohře) Rift is interlinked with the fault systems of the Variscian basement. In the Cheb Basin, the minimum CO2 flux is about 160 m3 h−1, with a diminishing trend towards the north and ceasing in the main epicentral area of the Northwest Bohemian swarm earthquakes. The ascending CO2 forms Ca‐Mg‐HCO3 type waters by leaching of cations from the fault planes and creates clay minerals, such as kaolinite, as alteration products on affected fault planes. These mineral reactions result in fault weakness and in hydraulically interconnected fault network. This leads to a decrease in the friction coefficient of the Coulomb failure stress (CFS) and to fault creep as stress build‐up cannot occur in the weak segments. At the transition zone in the north of the Cheb Basin, between areas of weak, fluid conductive faults and areas of locked faults with frictional strength, fluid pressure can increase resulting in stress build‐up. This can trigger strike‐slip swarm earthquakes. Fault creep or movements in weak segments may support a stress build‐up in the transition area by transmitting fluid pressure pulses. Additionally to fluid‐driven triggering models, it is important to consider that fluids ascending along faults are CO2‐supersaturated thus intensifying the effect of fluid flow. The enforced flow of CO2‐supersaturated fluids in the transitional zone from high to low permeability segments through narrowings triggers gas exsolution and may generate pressure fluctuations. Phase separation starts according to the phase behaviour of CO2‐H2O systems in the seismically active depths of NW Bohemia and may explain the vertical distribution of the seismicity. Changes in the size of the fluid transport channels in the fault systems caused, or superimposed, by fault movements, can produce fluid pressure increases or pulses, which are the precondition for triggering fluid‐induced swarm earthquakes.